Coseismic displacement waveforms for the 2016 August 24 Mw 6.0 Amatrice earthquake (central Italy) carried out from High-Rate GPS data - Antonio Avallone; Diana Latorre; Enrico Serpelloni; Adriano Cavaliere; André Herrero; Giampaolo Cecere; Nicola D'Agostino; Ciriaco D'Ambrosio; Roberto Devoti; Roberta Giuliani; Maurizio Mattone; Stefano Calcaterra; et al. (Annals of Geophysics, 2016)
We used High-Rate sampling Global Positioning System (HRGPS) data from 52 permanent stations to retrieve the coseismic dynamic displacements related to the 2016 August 24 Mw 6.0 Amatrice earthquake. The HRGPS position time series (named hereinafter "GPSgrams") were obtained with two different analysis strategies of the raw GPS measurements (Precise Point Positioning [PPP] and Double-Difference [DD] positioning approaches using the Gipsy-Oasis II and the TRACK (GAMIT/GLOBK) software, respectively). These GPSgrams show RMS accuracies mostly within 0.3 cm and, for each site, an agreement within 0.5 cm between the two solutions. By using cross-correlation technique, the GPSgrams are also compared to the doubly-integrated strong motion data at sites where the different instrumentations are co-located in order to recognize in the GPSgrams the seismic waves movements. The high values (mostly greater than 0.6) of the cross-correlation functions between these differently-generated waveforms (GPSgrams and the SM displacement time-histories) at the co-located sites confirm the ability of GPS in providing reliable waveforms for seismological applications.